Screening for personality disorder with the Standardised Assessment of Personality: Abbreviated Scale (SAPAS): further evidence of concurrent validity - Hesse, Morten (BioMed Central, 2010)
BACKGROUND: The assessment of personality disorders (PD) is costly and time-consuming. There is a need for a brief screen for personality disorders that can be used in routine clinical settings and epidemiological surveys. Aims: To test the validity of the Standardised Assessment of Personality: Abbreviated Scale (SAPAS) as a screen for PD in a clinical sample of substance abusers. METHODS: Convergent validity of the SAPAS with both categorical and dimensional representations of personality disorders was estimated. RESULTS: In this sample, the SAPAS correlated well with dimensional representations of cluster A and C personality disorders, even after controlling for ADHD symptoms, anxiety/depression symptoms and recent substance use. The SAPAS was also significantly associated with total number of PD criteria, although correlation with categorical measures of PD was weak. CONCLUSIONS: The SAPAS is an valid brief screen for PD as assessed dimensionally.